Sovereignty of Member States in New European Pact for Migration and Asylum - Wójcik, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the article attempts to analyze the consequences for Member States` sovereignty arising from the European asylum system reform and harmonization proposed in September 2020 by the European Commission. The author believes that so-called solidarity mechanism, however designed with intention of burden sharing and help, de facto has the potential to become migrant relocation mechanism.
Keywords: Common European Asylum System (CEAS); immigration; return procedures; asylum seekers; refugees; European Union migration policy; Dublin Regulation; sovereignty; migration crisis